Widespread promiscuous alkaline phosphatases underscore ancient microbial phosphite utilization - Morito Sakuma; Naoki Konno; Sevan Gholipour; John Z. Chen; Nobuhiko Tokuriki (Proceedings of the National Academy of Sciences, 2025)
Phosphate is often a limiting resource, directly affecting the availability of key biomolecules such as nucleotides. To cope with phosphate scarcity, bacteria have evolved enzymes that utilize alternative phosphorus compounds, including phosphite (Pt). Although a few enzymes oxidize Pt to produce phosphate, the enzymes responsible for Pt oxidation in many environmental bacteria remain unidentified, and the role of microbial Pt oxidation in the global phosphorus cycle is not yet fully understood. In this study, we performed bioinformatic analyses of three Pt-oxidizing enzymes: the native Pt oxidase, phosphite dehydrogenase (PtxD), and two promiscuous Pt oxidases, alkaline phosphatase (PhoA) and carbon–phosphorus lyase. Among these, PhoA was found to be widely distributed across bacteria since the early stages of their evolution. In contrast, PtxD emerged later in a limited number of bacterial lineages that had lost PhoA. Our biochemical characterizations revealed that most extant and reconstructed ancestral PhoAs tested exhibited Pt oxidation activity. Moreover, disruption of active-site residues diminished Pt oxidase activity in PhoA, while only partially affecting its native function. This promiscuous function of PhoA reveals an overlooked mechanism in bacterial phosphate metabolism and underscores the role of Pt in the cycling of bioavailable phosphorus in ecosystems.